In-vitro performance of a low flow extracorporeal carbon dioxide removal circuit. (April 2020) - Barrett, Nicholas A; Hart, Nicholas; Camporota, Luigi
Introduction: Extracorporeal gas exchange requires the passage of oxygen and carbon dioxide (CO2 ) across an artificial membrane. Current European Union regulations do not require the transfer to be assessed in models using clinically relevant haemoglobin, making it difficult for clinicians to understand the CO2 clearance of a membrane, and how it changes in relation to sweep gas flow through the membrane. The characteristics of membrane CO2 clearance are described using a single membrane at different sweep gas flows in an in vitro model with clinically relevant haemoglobin concentrations using three separate methods of calculating CO2 clearance. Methods: To define the CO2 removal characteristics of the extra-corporeal CO2 removal (ECCO2 R) device, we devised an in-vitro gas exchange circuit formed by a dedicated ECCO2 R circuit (ALung, Pittsburgh, USA) in series with two membrane oxygenators. The system was primed with donated expired human red cells provided by the local blood bank. The experimental set-up allowed constant CO2 input (via one membrane oxygenator) with variable removal from a portion of the blood in a manner which was analogous to that seen in vivo . Blood gases were measured from different ports in the circuit in order to measure the experimental membrane CO2 clearance (VCO2 ). Results: Results demonstrate that the relationship between VCO2 and gas flow at a constant blood flow of 0.4 L/minute with a haemoglobin of 7 g/dL increases sharply from a gas flow of 0 to 2 L/min but plateaus at gas flows >4 L/minute. VCO2, calculated using three different methods, showed a strong linear correlation with minimal bias. Conclusions: The CO2 clearance of the membrane used in this bench test is non-linear. This has implications for clinical practice, especially during the weaning phase of the device.